Dakwah Bil Haal Pondok Pesantren Al-Mutawally Di Desa Bojong Kecamatan Cilimus Kabupaten Kuningan - Asikin, Asikin; Mausul, Asep Ahmad (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2020)
The purpose of this study is to describe the form of da'wah activity of bil haal Al-Mutawally Islamic Boarding School, and to find out the goals, targets and supporting and inhibiting factors carried out fromda'wah activities at bil haal Al-Mutawally Islamic Boarding School in Bojong Village, Cilimus District, Kuningan Regency. This study uses a qualitative method. The data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The data analysis technique used in this study is a qualitative descriptive analysis technique. Meanwhile, the validity of the data was checked using the source triangulation technique. The results of this study indicate that: 1) Al-Mutawally Islamic Boarding School in carrying out its da'wah uses bil-lisan, bil-qolam and bil-haal da'wah, but what is more dominant isda'wah bil-haal such as providing scholarships, giving zakat and compensation for orphans . 2) The supporting factors of theda'wah activities bil-haal carried out by the Al-Mutawally Islamic Boarding School are the charismatic nature of the Al-Mutawally Islamic Boarding School Leaders, so that the community's response to the existence of the Al-Mutawally Islamic Boarding School is quite good. 3) The goals and objectives of the da'wah activities of the Al-Mutawally Islamic Boarding School are to create a quality, spiritual and intellectual condition of the surrounding community as the formation of civil society and build a community of faith and piety to Allah and His Messenger.